Industrial training report: Millennium Radius Sdn. Bhd. / Mohammad Nabil Abdul Rahman - Abdul Rahman, Mohammad Nabil (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about a thorough summary of my experiential learning during my internship at Millennium Radius Sdn. Bhd., a reputable company that specialises in information technology. I actively participated in tasks and projects that improved my professional knowledge, practical skills, and problem-solving abilities during the eight weeks training term. The report outlines the duties I oversaw, including developing a website by coding and software testing. Through these tasks, I was able to relate academically taught theoretical notions to practical problems. Working closely with divisions such as Software Developers and Software Testers, I was able to acquire knowledge on cooperative work settings and successful communication techniques. This report also discusses the challenges faced during the training, the solutions found, and the main results attained. It highlights the developed practical talents such as coding to create a website. This report serves as a witness to the life-changing learning and transformative development I underwent while working at Millennium Radius Sdn. Bhd., since it not only strengthened my grasp of industry processes but also prepared me for future professional tasks.